Establishment and optimization of a new model organism to study early land plant evolution: Germination, cultivation and oospore variation of Chara braunii Gmelin, 1826 - Holzhausen, Anja; Stingl, Nora; Rieth, Sophie; Kühn, Christine; Schubert, Hendrik; Rensing, Stefan Andreas (Frontiers in Plant Science, 2022)
For studying land plant evolution, the establishment and optimization of model organisms representing streptophytic algae, sister to land plants, is essential. Long-term cultivation experiments with Chara braunii S276 were performed over 8 years, since 3.5years under constant conditions. Additionally, short-term experiments for optimization of culture conditions were performed with three strains of C. braunii (S276, NIES-1604 and Lausiger Teiche, LaT-2708). Germination success after application of sterilisation agents, addition of gibberellic acid and under different incubation conditions with respect to pre-treatment, irradiance regime and substrate was investigated in order to develop protocols for generative cultivation of at least unialgal cultures. The resulting cultivation protocols for C. braunii S276, allowing maintenance of vegetative as well as generative cultures are presented in detail, including protocols for germination induction and growth of sterilized and unsterilized oospores.